2007
DOI: 10.1021/ic062231y
|View full text |Cite
|
Sign up to set email alerts
|

Ta3AlC2 and Ta4AlC3 − Single-Crystal Investigations of Two New Ternary Carbides of Tantalum Synthesized by the Molten Metal Technique

Abstract: Single crystals of the new ternary carbides Ta4AlC3 and Ta3AlC2 were synthesized from molten aluminum and characterized XRD, EDX, and WDX measurements. Crystal structures were refined for the first time on the basis of single-crystal data. Both compounds crystallize in a hexagonal structure with space group P63/mmc and Z = 2. The lattice constants are a = 3.1131(3) A and c = 24.122(3) A for Ta4AlC3 and a = 3.0930(6) A and c = 19.159(4) A for Ta3AlC2. The crystal structures can be explained with a building bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 36 publications
(34 reference statements)
9
70
0
3
Order By: Relevance
“…For Ta 5 AlC 4 , the Fermi-level is located at a very sharp peak and this is consistent with the fact that successful synthesis of Ta 5 AlC 4 has never been reported. 46 Our predictions of the contrasting stability of Ti 2 SC and Ti 2 PC crystals are consistent with the calculations by Du et al 16 and Hug et al 37 . Nevertheless, for those other phases, their less salient DOS topography at the Fermi-level could be outweighed by other factors in determining the phase stability, especially further in predicting whether a phase can exist or not.…”
Section: Methods Of Calculationsupporting
confidence: 91%
“…For Ta 5 AlC 4 , the Fermi-level is located at a very sharp peak and this is consistent with the fact that successful synthesis of Ta 5 AlC 4 has never been reported. 46 Our predictions of the contrasting stability of Ti 2 SC and Ti 2 PC crystals are consistent with the calculations by Du et al 16 and Hug et al 37 . Nevertheless, for those other phases, their less salient DOS topography at the Fermi-level could be outweighed by other factors in determining the phase stability, especially further in predicting whether a phase can exist or not.…”
Section: Methods Of Calculationsupporting
confidence: 91%
“…However, our data on Ta 4 AlC 3 powder showed that Ta 4 AlC 3 has the same structure as Ti 4 AlN 3 [38]. Etzkorn et al [39] independently arrived at the same conclusion. We attempted to refine our XRD data to the structure proposed by Lin et al; however, this refinement was not possible since the experimental peak intensities differed strongly from the calculated intensities, in many cases by more than an order of magnitude.…”
Section: Polymorphism Of Max Phasesmentioning
confidence: 49%
“…In the first reports on Ti 4 AlN 3 [28], the stoichiometry was stated to be Ti 4 AlN 3- with  ≈ 0.1 (determined from Rietveld refinement of Xray and neutron diffraction data), i.e., the Ti 4 AlN 3 structure was reported to be slightly substoichiometric in N. This is supported by DFT calculations, which indicate that introduction of N vacancies in Ti 4 AlN 3- is energetically favorable compared to stoichiometric Ti 4 AlN 3 [52]. On the other hand, a recent calculation for -Ta 4 AlC 3 by Du et al [53] indicated that the introduction of only a small amount of C vacancies in Ta 4 AlC 3 results in reduced stability compared to the stoichiometric structure, and there are no experimental indications that -Ta 4 AlC 3 is understoichiometric in C [39]. Therefore, it is possible that the X-site vacancy-bearing abilities of the known 413 phases differ.…”
Section: Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…From Density Functional Theory (DFT) calculations, it has been predicted that the introduction of N or C vacancies in Ti 4 AlN 3−δ and V 4 AlC 3- , respectively, increases the phase stability relative to the stoichiometric 413 phases [18,19]. In contrast, a similar calculation for α-Ta 4 AlC 3 suggested that a small amount of C vacancies in Ta 4 AlC 3 reduces the stability compared to the stoichiometric structure [20], and there are no experimental indications that α-Ta 4 AlC 3 is understoichiometric in C [21][22]. Nevertheless, there is most likely a stoichiometry range for X-site vacancies for most MAX phases, as for the binary carbides and nitrides.…”
Section: Introductionmentioning
confidence: 98%